Strategies of Monetary and Fiscal Policy Mix to Mitigate Global Uncertainty in North Sumatra - Shihab, Muhammad Wahyu; Syafii, M. (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
Global uncertainty poses significant challenges for the North Sumatra economy, which requires an appropriate monetary and fiscal policy mix strategy to mitigate its negative impact. This study aims to analyze how interest rate, tax, and government spending (APBN) policies affect exports, imports, and Gross Regional Domestic Product (GRDP) in North Sumatra. Using a path analysis approach with secondary data from 2014 to 2023, this study found that government spending has a significant influence on GRDP, while interest rates and taxes do not have a meaningful impact. In addition, the analysis shows that exports and imports function as intervening variables between monetary and fiscal policies on GRDP, but with limited contribution. These findings underscore the importance of government spending in maintaining regional economic stability, especially in the context of global uncertainty. Suggestions are given to the North Sumatra government to pay attention to the effectiveness of APBN spending and encourage the improvement of the competitiveness of local MSMEs to reduce dependence on imports. This research contributes to the local economic literature and offers relevant policy recommendations to strengthen North Sumatra’s economic resilience.